Algorithm Development to Predict the Dynamic Characteristic of a Multi Rotor System - Amir Zaki Mubarak (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Rotor systems have been widely used in mechanical applications in industry andeven in daily live equipments. The motion effects of the rotor in certain cases can cause discomfort to the user even can cause of failure to the system itself. Therefore the dynamic characteristic analysis of the system is very essential to be analysed in designing a rotor system. By the development of computer technology, the analysis can be straightforwardly performed through numeric method by utilizing existing computational software, i.e. MATLAB. Existing researchers have developed the algorithm to analyse the dynamiccharacteristic of Jeffcot rotor and dual rotor systems by using MATLAB. The objective of this research is to conduct further investigation in developing algorithm to predict the dynamic characteristic of a multi rotor system. The analysed rotor system consists of a rotor shaft and several disks. The analysis is conducted for a variation number of disk. The equation of motion of the system is derived based on the potential and kinetic energy of the system. Lagrange‟s equation is then applied to the equation of motion that it can be solvednumerically. Based on the equation of motion, a computational algorithm is then developed to determine the natural frequency of the rotor shaft which is the main objective of this research. The algorithm is developed and simulated in MATLAB. The simulation result is closed with theoretical analysis.